Juvenile Mitral Stenosis Presenting as Acute Pulmonary Edema Treated with Balloon Mitral Valvotomy - Newton Ghosh; Priyavardhan Mishra; Kshitij Balwaik; Anant Patil (Heart Views)
Juvenile mitral stenosis is defined by poor left atrial emptying due to limited opening of the mitral-valve orifice in patients under the age of 20 years. Balloon mitral valvotomy is the current treatment of choice for juvenile mitral stenosis. Here we report a case of a 14-year-old female presenting with signs of acute pulmonary oedema. Later on, underlying mitral stenosis was revealed on echocardiography. After evaluation, she was successfully managed by percutaneous balloon mitral valvotomy. Screening young patients with pulmonary oedema by two-dimensional echocardiography is necessary to evaluate the underlying cardiac cause.